The Effectiveness of the Work From Home (WFH) Program during the Covid-19 Pandemic - Mendrika, Vatosoa; Darmawan, Didit; Anjanarko, Tri Seno; Jahroni,; Shaleh, Mochamad; Handayani, Budi (Journal of Social Science Studies, 2021)
The direct impact of Covid-19 is the weakening of economic growth or even the economy experiencing negative growth. Gross domestic product has decreased drastically. Covid-19 has forced all of us to migrate from places of work in offices, places to study at schools, places to shop at malls, even places of worship in places of worship to all being done at home. The readiness of workers to adapt due to changes in the work environment and different conditions in general is also a challenge for both workers and companies. Therefore, researchers conducted research on the implementation of employee WFH. This research is a quantitative research. The data collection technique is through literature study which aims to describe, explain and analyze facts that can support the research topic. The results show that remote work can be an answer to urban issues and emergency conditions in the short and long term. However, remote work has not yet become mainstream in modern human life.